Pengaruh Nilai Tukar Rupiah dan Bath terhadap Dolar serta Suku Bunga Indonesia terhadap Nilai Ekspor Indonesia ke Thailand Periode 2000-2019 - Sugiartiningsih, Sugiartiningsih (WELFARE Jurnal Ilmu Ekonomi, 2021)
This study aims to determine the effect of the rupiah exchange rate against the US dollar, bath against the US dollar and Indonesian interest rates on Indonesian exports to Thailand for the period 2000-2019. The research methodology uses a multiple regression model of the relationship between the two Indonesian exchange rates and interest rates with the value of Indonesia's exports to Thailand. The use of data starting in 2000 with the reason that post-reform is the dynamics of Indonesia in responding to economic globalization. The 2019 limit is to provide a real picture of the Indonesian economy before it was hit by the Covid-19 outbreak. Based on the calculation results, it was found that there was a positive relationship between the rupiah exchange rate against the US dollar and the value of Indonesia's exports to Thailand due to the high purchasing power of Thailand as a result of the decline in the rupiah exchange rate against the US dollar. On the other hand, the bath exchange rate which tends to appreciate against the US dollar actually increases the value of Indonesia's exports to Thailand. Likewise, a decrease in Indonesia's interest rates has the potential to increase economic productivity in the real sector and in turn increase the value of Indonesia's exports to Thailand. However, the amount of investment during the period studied was not optimal due to lack of trust in Indonesia that caused the results of the test conducted were not significant.Penelitian ini bertujuan untuk mengetahui pengaruh nilai tukar rupiah dan bath terhadap dolar AS serta suku bunga Indonesia terhadap ekspor Indonesia ke Thailand periode 2000-2019. Metodologi penelitian menggunakan model regresi berganda hubunganÂ  kedua nilai tukar dan suku bunga IndonesiaÂ  dengan nilai ekspor Indonesia ke Thailand. Penggunaan data mulai tahun 2000 dengan alasan pasca reformasi merupakan dinamisasi Indonesia merespon globalisasi ekonomi. Batasan tahun 2019 untuk memberikan gambaran riil perekonomian Indonesia mengalami pandemi Covid-19. Berdasarkan hasil perhitungan diperoleh hubungan positif nilai tukar rupiah terhadap dolar AS dengan nilai ekspor Indonesia ke Thailand karena tingginya daya beli Thailand sebagai dampak penurunan nilai tukar rupiah terhadap dolar AS. Sebaliknya nilai tukar bath yang cenderung apresiasi terhadap dolar AS justru meningkatkan nilai ekspor Indonesia ke Thailand. Demikian halnya dengan penurunan sukubunga Indonesia berpotensi meningkatkan produktivitas ekonomi di sektor riil dan pada gilirannya meningkatkan nilai ekspor Indonesia ke Thailand. Namun demikian, besarnya penanaman modal selama periode yang diteliti belum optimal karena kurangnya kepercayaan terhadap Indonesia sehingga berdampak hasil uji yang tidak signifikan.